2018
DOI: 10.3389/fgene.2018.00353
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Multiple Primary Tumors in Atypical Presentation of Cowden Syndrome Identified by Whole-Exome-Sequencing

Abstract: A family with an aggregation of rare early onset multiple primary tumors has been managed in our oncogenetics department: the proband developed four early onset carcinomas between ages 31 and 33 years, including acral melanoma, bilateral clear cell renal carcinoma (RC), and follicular variant of papillary thyroid carcinoma. The proband’s parent developed orbital lymphoma and small intestine mucosa-associated lymphoid tissue (MALT) lymphoma between 40 and 50 years old. Whole-exome-sequencing (WES) of the nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…Based on these results, screening for kidney cancer was recommended to begin at 33 years of age to capture 95% of cases, or at 28 years of age (the youngest reported case) to capture 100% of cases 22 . Lowering the age of surveillance to 30 years of age for CS-RCC has been suggested in more recent reports as well 8,13 . A study at the Institut Bergonié Genetic Laboratory (Bordeaux, France) identified 146 individuals with deleterious germline PTEN pathogenic variants and detailed phenotypic information 8 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Based on these results, screening for kidney cancer was recommended to begin at 33 years of age to capture 95% of cases, or at 28 years of age (the youngest reported case) to capture 100% of cases 22 . Lowering the age of surveillance to 30 years of age for CS-RCC has been suggested in more recent reports as well 8,13 . A study at the Institut Bergonié Genetic Laboratory (Bordeaux, France) identified 146 individuals with deleterious germline PTEN pathogenic variants and detailed phenotypic information 8 .…”
Section: Discussionmentioning
confidence: 95%
“…It was hypothesized that rare tumours in these children resulted from combined pathogenic variants in tumour suppressor genes/oncogenes and PTEN, but no suggestions for updating surveillance criteria for CS-RCC were given 23 . Finally, an atypical presentation of CS, where the proband did not meet diagnostic or testing criteria, identified four tumours within two years from 31 to 33 years of age 13 . This included acral melanoma, a follicular variant of papillary thyroid carcinoma, and two clear cell RCCs 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These approaches often rely on manual variant prioritization from candidate variants by human. In such process, human experts infer functional similarity between the candidate variants and the target causal mutation by reviewing relevant knowledge-bases [41,[111][112][113]. Incorporation of a computational method that can comprehensively analyze and prioritize modifiers from candidate modifier variants is still an open area for research.…”
Section: Wgs Approach For Modifier Studiesmentioning
confidence: 99%